Pengaruh Tingkat Partisipasi Angkatan Kerja, Pertumbuhan Penduduk, Rata-Rata Lama Sekolah dan Upah Minimum Terhadap Tingkat Pengangguran Terbuka di Provinsi Jawa Barat - Mutafikatul Khoiriyah; Niniek Imaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The Open Unemployment Rate (TPT) in West Java Province is a crucial macroeconomic indicator that requires in-depth analysis considering the demographic and industrial dynamics in the region. This study aims to analyze the simultaneous and partial effects of the Labor Force Participation Rate (TPAK), Population Growth, Average Years of Schooling (RLS), and Provincial Minimum Wage (UMP) on the TPT in West Java during the period 2009–2023. Using a quantitative method with a causality approach and correlational design, secondary time series data were analyzed using Multiple Linear Regression. The results of the simultaneous test (F Test) show that the four independent variables together have a significant effect on the TPT, with a contribution of 51.6% (Adjusted R2 = 0.516). Partially (t Test), it was found that: (1) TPAK does not have a significant effect on the TPT; (2) Population Growth has a significant and negative effect, reflecting its role as a stimulus for Aggregate Demand; (3) RLS has a significant and positive effect, indicating the phenomenon of educated unemployment or skill mismatch; and (4) the UMP has a significant and negative effect, confirming its role as a Keynesian purchasing power stimulus instrument and is the most dominant variable. In conclusion, unemployment in West Java is driven by structural challenges (educational mismatch) which are offset by the effectiveness of the UMP as a purchasing power stabilization policy, but is not significantly influenced by the rate of individual labor force participation. The implication is that policy should focus on reorienting vocational education and maintaining a strategic minimum wage policy.